An overview of wireless sensor network and its applications - Khalid Waleed Al-ani; Ahmed Subhi Abdalkafor; Aiman Majid Nassar (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Small devices that can sense and collect data from the surrounding environment have been produced with the rapid development of wireless technology and digital electronics. As a result, a wireless sensor network (WSN) was constructed from these sensor devices to send collected data to the base station for monitoring and analysis. This paper provides an overview of WSN, as well as its architecture and applications.